Networks-on-chip : from implementations to programming paradigms - Ma, Sheng; Huang, Libo, 1976-; Lai, Mingche; Shi, Wei (Morgan Kaufmann, 2014)
Networks-on-Chip: From Implementations to Programming Paradigms provides a thorough and bottom-up exploration of the whole NoC design space in a coherent and uniform fashion, from low-level router, buffer and topology implementations, to routing and flow control schemes, to co-optimizations of NoC and high-level programming paradigms. This textbook is intended for an advanced course on computer architecture, suitable for graduate students or senior undergrads who want to specialize in the area of computer architecture and Networks-on-Chip. It is also intended for practitioners in the indust.